The value of BAP1 immunocytochemistry and CDKN2A fluorescence in situ hybridization in diagnosis of serous effusion malignant mesothelioma and an analysis of the association between degree of cell atypia and the results of two auxiliary methods - Ren, Wenhao; Zhao, Lin-lin; Guo, Lei; Lu, Ning; Cao, Jian (Polish Journal of Pathology, 2020)
Malignant mesothelioma (MM) is a rare, highly aggressive tumor. The first symptom of MM is mostly serous effusion, and cytology can be used in diagnosis based on effusion, providing patients with an earlier diagnosis and treatment opportunity. A total of 67 specimens were embedded into cell blocks, and BAP1 immunocytochemistry (ICC) was performed. CDKN2A fluorescence in situ hybridization (FISH) was performed in 45 cases. The sensitivity, specificity and the association between the degree of cell atypia and the results of two auxiliary methods were analyzed. BAP1 ICC showed nonexpression in 13 of 24 cases of MM and 0 of 21 cases of benign mesothelial proliferation (BMP). The sensitivity was 54.2% (13/24), and the specificity was 100% (21/21). In addition, 22 metastatic adenocarcinoma (MA) cases all showed BAP1 expression. MM with BAP1 expression had more obvious cell atypia. CDKN2A deletion was found in 12 of 24 MM cases and 0 of 21 BMP cases. The sensitivity was 50% (12/24), and the specificity was 100% (21/21). BAP1 ICC and CDKN2A FISH are useful methods to differentiate MM from BMP. The cell atypia of MM with BAP1 expression was more obvious than MM with BAP1 nonexpression.